Adjustment strategies amongst black African and black Caribbean men following treatment for prostate cancer: Findings from the Life After Prostate Cancer Diagnosis (LAPCD) study. (23rd October 2019) - Wagland, Richard; Nayoan, Johana; Matheson, Lauren; Rivas, Carol; Brett, Jo; Collaco, Nicole; Alexis, Obrey; Gavin, Anna; Glaser, Adam W; Watson, Eila
Abstract: Objective: To explore adjustment strategies adopted by Black African (BA) and Black Caribbean (BC) men in the UK as a response to the impact of PCa diagnosis and treatment effects. Methods: Men were recruited through the UK‐wide 'Life After Prostate Cancer Diagnosis' (LAPCD) survey. Telephone interviews were conducted with men ( n = 14) with BA and BC backgrounds between 18 and 42 months post‐diagnosis. Data were analysed using a Framework approach. Results: Most men ( n = 12) were born outside the UK, were married ( n = 9) and employed ( n = 9). Median age was 66 years (range: 55–85). Six overarching themes emerged: a strong reliance upon faith beliefs; maintaining a 'positive' front; work as distraction; non‐disclosure of diagnosis even amongst family members, influenced by stigma and masculinity concerns; active awareness‐raising amongst a minority and support‐seeking from close community. A few men emphasised a need to 'pitch' awareness‐raising messages appropriately. Potential links existed between faith beliefs, presenting a positive front, community support‐seeking and local awareness‐raising. Conclusion: The provision of patient‐centred care requires cultural sensitivity. Interventions that challenge stigma and men's reluctance to disclose problems associated with PCa and treatment may encourage help‐seeking for symptom support. Research is needed to determine how best awareness‐raising messages should be conveyed to black men.